Impact Of Measurement Of Service Quality Using The Servqual Method: Case Study In Pt. Karya Mandiri Sepakat Surabaya - Achmad Daengs GS; Moch. Rizaldy Rahmansyah; Rina Dewi; Diana Zuhro; Indriana Kristiawati (Digital Innovation : International Journal of Management, 2024)
The research for this thesis takes the title: "Measurement of Service Quality at PT. Karya Mandiri Sepakat Surabaya Using the SERVQUAL Method”. The aim of conducting this research is to determine the quality of service provided at PT. Karya Mandiri agrees to all customers in terms of 5 service dimensions and to determine the efforts made to improve the quality of PT service. Karya Mandiri Agreed to retain customers. The analytical tool used in this research is the SERVQUAL method. From the research results, it is known that the gaps for the Physical Facilities dimension have the smallest gap value, namely - 0.80 in the third item, namely for the question employees must look attractive and neat, for the Reliability Dimension the smallest gap value is in the fifth item. amounting to - 1.78, namely for questions, a quality office will require the data to be free from errors, for the responsiveness dimension, the smallest gap value is in the thirteenth item, amounting to - 2.52, namely for questions, employees will provide service quickly to customers, for the dimension confidence has the smallest gap value in the sixth item of - 0.56, namely for the question Employees are consistently respectful, patient and friendly towards their customers, for the empathy dimension the smallest gap value is in the twenty second item of - 0.72 namely for questions, employees understand the special needs of each customer who comes.